Applications for Green Technology Practices in Analyzing the Edge Detection Techniques on Digital Image Processing by using MATLAB. Issue 1 (1st August 2022) - Ravikumar, R.; Arulmozhi, V.
Abstract: Increasing awareness and growing focus on environmental issues such as climate change, energy use, and the loss of non-renewable resources have created a great need for research that provides possible solutions to these problems. Environmental science and engineering research continue to play an important role in revealing new "green" future opportunities. Digital Image Processing plays a major role in contributing to its relevant research works under these Environmental and Green Technologies. By applying tools related to Environment technology this Digital Image Processing produces numerous applications. In such cases, Edges provide an important dynamic change in digital image processing. It is a process of finding and finding edges with sharp changes made by the power of its images. This is the best way to get an accurate edge in good shape and also different edge finders will work in better different conditions. Different methods of edge detection were compared comparatively to determine which method was most suitable for obtaining edges without any noise conditions. Here, the three types of edges have horizontal, vertical and diagonal edges. In this paper, we review the different editing methods and compare different identification methods, advantages, and disadvantages. Implementation is done using MATLAB. A sudden change of discontinuity is evident in the image.